Perspectives of the wood-based industry on chain of custody certification in Sabah - Michelle Boyou; Liew, Kang Chiang (e-VIBS, Faculty of Science and Natural Resources, 2019)
Chain of Custody (CoC) Certification is part of the forest certification that ensures the wood products purchased can be tracked accurately back to its source in the forest. This study was done to determine the current status and the implementation of CoC Certification in the wood-based industries in Sabah. Two populations were identified, which are those holding a CoC certificate and those who do not possess a CoC certificate. Questionnaires were developed with respondents’ opinion and perception regarding forest certification focusing on COC Certification in Sabah. Distribution of questionnaire forms to the industry players related to wood-based industries and interview sessions was conducted with the person-in-charge of the Chain of Custody system. Results indicated that there are low percentage of the industries that possesses CoC Certification and have low knowledge regarding CoC Certification and its benefits. This is because the industry players are mainly targeting for local consumers and certification is not required. Others stated that the cost to obtain CoC Certification is too high with low to no benefit to the industry, while others stated that certification has no importance in terms of market benefits. Most of the wood-based industries in Sabah has low awareness regarding the importance of CoC Certification, hence the low number of companies that holds the certificate. The absence of government support, lack of training, lack of market benefit and price premium are also the factors that influences the low number of certificate holders.